STYLISTICS AND REGISTER AS CORE DETERMINANTS OF MEANING IN LANGUAGE AND TRANSLATION - Ismoilova Shaxrizoda Sanjar qizi,; Zarnigor Hasanova Ixtiyor qizi, (TADQIQOTLAR, 2026)
shaxrizoda909@gmail.com   Abstract This  article  examines  stylistics  and  register  as  fundamental  determinants  of meaning in language and translation, arguing that meaning is not an inherent property of words or grammatical structures but is constructed dynamically through contextual, functional,  and  stylistic  choices.  Drawing  on  functional  linguistics  and  translation theory, the study demonstrates that stylistic variation encodes attitudes, emotions, and cultural values, while register organizes language according to situational parameters such as field, tenor, and mode. Through detailed theoretical discussion and illustrative examples, the paper shows that translation requires not only semantic equivalence but also  the  reconstruction  of  stylistic  and  register-based  meaning.  The  article’s contribution lies in its systematic integration of stylistics and register into a unified framework  for  understanding  meaning,  highlighting  their  inseparability  in  both linguistic analysis and translation practice.